Production of Brikueda (Briquettes from Teak Sawdusts and Durian Rind/Durio zibethinus) as Renewable Fuels - Wihdatus Syarifah; Sulhadi Sulhadi; Teguh Darsono (Journal of Natural Sciences and Mathematics Research, 2019)
Jepara is a carving city. The result of carving produces sawdust waste which is usually used to be sold and burned. In addition, durian fruit is available that has a distinctive taste and made an icon of one village in Jepara. The fruit is the belle of the whole community to be eaten by meat and made food. But the skin has the traits and characters that are difficult to decompose. Then the two wastes will be combined with tapioca flour into briquettes as an alternative fuel. This research take four stage: combustion, filtering, printing, and drying. Obtained two treatment, the first treatment is using ratio wood sawdust and durian rind; 50 gr: 50 gr; 25 gr: 50 gr; 50 gr: 25 gr. The results shown it does not ignite up and very hard. The second treatment is using same ratio but added 25 gram starch, the results shown it ignite. This is due to the starch content is used, it ignite the longest with a concentration ratio of 50 gr: 50 gr because its combination increases the calories value. In durian rind there are 3786 cal/g and teak wood consists mainly of cellulose (40-50%), hemicellulose (20-30%), lignin (20-30%), and the calories value of sawdust briquettes is 4714-5519 kcal/kg.©2019 JNSMR UIN Walisongo. All rights reserved.